Marcadores inflamatórios influenciam o padrão locomotor durante a ultrapassagem de obstáculos em idosos com e sem histórico de quedas - Silva, Juliana Amaral da (2023)
Changes from the morphological, functional and biochemical point of view in the aging process compromise the elderly in walking, especially in obstacle avoidance. The analysis of factors related to obstacle crossing helps to identify locomotor strategies associated with the risk of falls (abrupt change of level with a high probability of comorbidities). In addition to the structural decline, the elderly undergoes a metabolic and enzymatic process called Inflammaging (chronic and low-grade systemic inflammation) that can favor the manifestation of injuries, such as the frailty syndrome. It is still not clear in the scientific literature whether inflammatory biomarkers influence the spatiotemporal parameters of gait in elderly people with and without a history of falls and whether these changes depend on the degree of difficulty of the task. The aim of this study was to investigate the influence of inflammatory biomarkers on the locomotor behavior of elderly people with and without a history of falls in the free walking task and when overcoming obstacles, and whether this relationship depends on the difficulty of the task. 22 elderly participated in this study and were divided into two groups: elderly who fall (n=11) and elderly who do not fall (n=11), evaluated in two stages: 1) Clinical Anamnesis and Gait Analysis and 2) Blood Collection and Analysis. At first, participants were invited to answer a clinical anamnesis (general health status and collection of anthropometric measurements) and underwent clinical tests to assess static and dynamic balance, cognitive level, questionnaire on falls and fear of falling and on physical activity. physics. After that, they were invited to walk on a 9 m long walkway, under two conditions: free walking and overcoming an obstacle. The level of difficulty of task was determined by the characteristic of the obstacle: solid (single block of foam) or fragile (smaller pieces of foam stacked, in the same size and shape as the solid obstacle), both with 15 cm in height. Two cameras were positioned to view all markers (right foot: fifth metatarsal and lateral surface of the calcaneus | left foot: first metatarsal and medial surface of the calcaneus). In the free walking task, the spacetime parameters (length, width, duration and speed) were evaluated. In the task of obstacle avoidance, the locomotor parameters were evaluated: length, width, duration and speed of the step and stride before overcoming, horizontal foot obstacle distance (DHPO), Vertical foot obstacle distance (DVPO), maximum foot elevation (ME) and Horizontal Obstacle-Foot Distance (DHOP) after obstacle crossing. In the second moment, blood collection (10 mL, in the morning and fasting) was performed for analysis of inflammatory biomarkers (Interleukin 6 and C-Reactive Protein) through the ELISA Immunoenzymatic Method. T-tests were performed to verify possible differences between the groups for clinical, anthropometric and IL-6 and CRP levels. Considering the fall as a confounding variable in the performance of motor behavior, 02 models were used for the regression analyses, as follows: I) model without adjustment; II) model adjusted by the number of falls. Multivariance analyzes were performed to verify possible differences between groups and conditions in locomotor performance tasks. The significance level for all analyzes was maintained at p≤0.05. The regression analysis showed significance only for the condition of overcoming obstacles. The C-Reactive Protein influences the DHPO variable for the approach limb, only for the fragile obstacle condition. The Interleukin 6 variable, in the regression analysis, influenced the variables: DHPO for the approach limb when solid obstacle, step width of the support limb for the solid obstacle condition, ME on the support limb for the solid and fragile obstacle condition and ME on the fragile obstacle condition for approach member. The inflammation process in the elderly is related to more challenging tasks, which indicates a conservative pattern due to the greater proximity of the obstacle to the approach limb and greater width and elevation of the support limb to optimize the task. The diagnostic association of clinical tests and laboratory tests to outline the inflammatory profile of the elderly can be a good preventive and follow-up strategy for the structural, functional and metabolic declines inherent to aging.